2018
DOI: 10.1088/1748-9326/aae7f9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of regulatory policy in curbing deforestation in a biodiversity hotspot

Abstract: Recent rates of deforestation on private lands in Australia rival deforestation hotspots around the world, despite conservation policies in place to avert deforestation. This study uses causal impact estimation techniques to determine if a controversial conservation policy-the Vegetation Management Act (VMA)-has successfully reduced deforestation of remnant trees in the Brigalow Belt South, a 21.6 Mha biodiversity hotspot in Queensland. We use covariate matching to determine the regulatory effect of the policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Our review identified just one study meeting our inclusion criteria that compared NNL outcomes with a robust counterfactual (Gibbons et al., ). Generally, the quality of impact evaluations for NNL appear to be lagging behind those applied in other areas of conservation and environmental policy, such as payments for ecosystem services (Pynegar, Jones, Gibbons, & Asquith, ), protected areas (Miteva, Pattanayak, & Ferraro, ), commodity sustainability certification (Carlson et al., ), and forest policy (Simmons et al., ). Recognizing that the true causal impact of conservation policies can be confounded by biases in those receiving conservation treatments, there is an increase in applications of experimental, quasi‐experimental, and matching methods to improve our causal understanding of policy effectiveness (Ferraro & Hanauer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our review identified just one study meeting our inclusion criteria that compared NNL outcomes with a robust counterfactual (Gibbons et al., ). Generally, the quality of impact evaluations for NNL appear to be lagging behind those applied in other areas of conservation and environmental policy, such as payments for ecosystem services (Pynegar, Jones, Gibbons, & Asquith, ), protected areas (Miteva, Pattanayak, & Ferraro, ), commodity sustainability certification (Carlson et al., ), and forest policy (Simmons et al., ). Recognizing that the true causal impact of conservation policies can be confounded by biases in those receiving conservation treatments, there is an increase in applications of experimental, quasi‐experimental, and matching methods to improve our causal understanding of policy effectiveness (Ferraro & Hanauer, ).…”
Section: Discussionmentioning
confidence: 99%
“…(2007) and Simmons et al . (2018)]. This approach is analogous to the procedure for selection of covariates described in Section IV.2.…”
Section: Applying Matching Methodsmentioning
confidence: 99%
“…We also assumed that the relatively strict vegetation clearing regulations observed between 2007 and 2014 influence clearing behaviour similarly throughout the projection period . While our analysis captures the effect of clearing regulations during the model calibration period (Evans, 2016;Marcos-Martinez et al, 2018), changes to such regulations could lead to forest cover changes well outside of the ranges presented here (Simmons et al, 2018c).…”
Section: Contributions and Caveatsmentioning
confidence: 99%